KAPABILITAS PEMERINTAH DAERAH KABUPATEN KUANTAN SINGINGI DALAM PENGELOLAAN RUANG TERBUKA HIJAU (RTH) TAHUN 2011-2015 - Maryuhembri "; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Green open space (RTH) in Kuantan Singingi managed by the local government through the Office of Market, Hygiene and in 2014 an area of 112.26 hectares with trees that have been planted 8.720 (average rat 78 trees per ha) situated in Taluk Kuantan as its capital. This study aims to identify and explain as well as factors that affect the capability of the government of Regency Kuantan Singingi in the Management of green open space (RTH) Year 2011-2015.This study uses qualitative research methods with descriptive research, which can be interpreted as a problem-solving process was investigated by describing the state of the research subjects were based on the facts that appear during the study were then followed by the popularity of existing theories.Based on the results of the study found the spread of green open space (RTH) is generally uneven. There is still a lack of green open space (RTH) in Kuantan Singingi the area of 122 ha, but local authorities are already working to make the creation of decent and green space as needed. The problem of budget constraints, human resources, infrastructure constraint Singingi Kuantan district government in the management of RTH maximum.Keywords: Capability, Management, Local Government